Multi-dynamic-bond synergistic self-repairing polyurethane and preparation method thereof
By introducing a multi-dynamic bond collaborative self-healing mechanism in polyurethane, using components such as pyridine, iron ions and catechol to form a complex crosslinking network, the problem of unstable performance of existing materials in harsh environments is solved, and efficient self-health Repair and excellent damping performance.
Patent Information
- Application Number
- CN202411569222.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing high-damping self-repair materials have unstable performance in harsh environments such as high temperature and humidity, and are prone to fatigue and aging during long-term use, making it difficult to achieve efficient self-repair under dynamic loading conditions.
Polyurethane that uses multi-dynamic bonds to self-heal, includes coordination bonds between pyridine and iron ions, coordination bonds between catechol and iron ions, and hydrogen bonds between polymer chains, forming complex intersections through these multi-stage dynamic chemical bonds. Connect the network to improve the self-repair ability and damping performance of the material.
It has achieved good self-repair ability and excellent damping performance at room temperature. The material can be automatically repaired after external damage, extends its service life, and shows higher stability and durability in harsh environments.
Smart Images

Figure CN119431720A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyurethane with multiple dynamic bonds and a preparation method thereof, belonging to the technical field of polyurethane. Background Art
[0002] Damping materials are a type of material that can absorb and disperse vibration energy. They are widely used in engineering structures, automobiles, aerospace and other fields to reduce vibration and noise and improve structural stability and comfort. Self-healing materials are a type of material with self-healing capabilities that can automatically repair after damage, extend the service life of the material and reduce maintenance costs. The research and development of materials with both damping and self-healing properties is of great significance to improving the functionality and performance of materials and promoting the development of materials science and engineering technology.
[0003] In the past few decades, the research on damping materials has made significant progress. Traditional damping materials mainly include metal damping materials, polymer damping materials and composite damping materials. However, the performance of traditional damping materials is often unstable in harsh environments such as high temperature and high humidity, and they are prone to fatigue and aging during long-term use, which limits their application in practical engineering. Therefore, seeking a new type of damping material has important research significance and application value.
[0004] Self-healing materials are one of the research hotspots in the field of materials science in recent years. Traditional self-healing materials mainly include microcapsule self-healing materials, conductive self-healing materials and chemical reaction self-healing materials. These materials have certain self-healing capabilities, but are often limited by problems such as material volume changes and low repair efficiency, making it difficult to achieve self-healing functions under dynamic loading conditions. Therefore, developing a new type of self-healing material with efficient self-healing performance and excellent dynamic mechanical properties is of great significance to promote the application and development of self-healing materials.
[0005] As a new type of damping material, high damping self-repairing polyurethane has unique advantages and potential application prospects. First of all, this material has excellent damping performance, can effectively absorb and disperse energy under dynamic loading, and reduce the vibration and noise of the structure. Secondly, it also has good self-repairing performance, can automatically repair after damage, extend the service life of the material, and reduce maintenance costs. Combining these advantages, materials with both damping and self-repairing properties have broad application prospects and have important application value in the fields of construction, transportation, aerospace, etc. However, there are still some bottlenecks in the existing high damping self-repairing materials. The preparation of high damping self-repairing polyurethane materials requires precise control of the composition, structure and micromorphology of the materials to ensure that they have good damping performance and self-repairing ability at the same time. This requires the preparation process to have a high degree of accuracy and stability, but the current technical level is still difficult to fully meet this requirement. While pursuing high damping performance, it is also necessary to ensure the self-repairing efficiency, mechanical properties and durability of the material. There is often a mutually restrictive relationship between these properties, making performance optimization particularly difficult. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a polyurethane with multi-dynamic bond synergistic self-repairing and a preparation method thereof. The polyurethane contains multiple dynamic bonds, including coordination bonds between pyridine and iron ions, coordination bonds between catechol and iron ions, and hydrogen bonds between polymer chains. When subjected to external pressure, the material has good damping capacity due to the internal friction inside the molecular chain; at the same time, the polyurethane has good self-repairing ability at room temperature.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] A polyurethane with multiple dynamic bonds for collaborative self-repairing. The raw materials of the polyurethane include polydiol, diisocyanate, pyridine chain extender, catechol and trivalent iron ion salt. Taking the total mass of the polydiol, diisocyanate, pyridine chain extender and catechol as 100%, the mass fraction of the polydiol is 46.65% to 54.24%, the mass fraction of the diisocyanate is 25.91% to 32.51%, the mass fraction of the pyridine chain extender is 9.72% to 13.59%, and the mass fraction of the catechol is 7.69% to 14.91%; the molar ratio of iron ions, pyridine chain extender and catechol is 1:2:3.
[0009] Preferably, the main chain of the polyurethane is formed by polydiol and diisocyanate after chain extension by a pyridine chain extender, the end group is exposed by a catechol group after end-capping by a catechol substance, and the trivalent iron ion forms a metal coordination bond with the catechol group on the one hand, and forms a coordination bond with the nitrogen atom on the pyridine on the other hand; wherein the coordination relationship between the iron ion and the catechol group is The coordination relationship of iron ion to pyridine is
[0010] Preferably, the polyglycol is one or more of polytetramethylene glycol (PTMG), polypropylene glycol (PPG) and polyethylene glycol (PEG).
[0011] Preferably, the molecular weight of the polyglycol is 1500-3000.
[0012] Preferably, the diisocyanate is one or more of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI) and L-lysine diisocyanate (LDI).
[0013] Preferably, the pyridine chain extender is 2,6-pyridine dimethanol or 2,6-pyridine dimethylamine.
[0014] Preferably, the catechol substance is one or more of dopamine (DA), isoproterenol (ISO), ellagic acid (EA) and quercetin (QR).
[0015] Preferably, the trivalent iron ion salt is one or more of nitrate, carboxylate and chloride.
[0016] Preferably, the tensile strength of the polyurethane is 0.9-3.5 MPa, the damping factor is 0.4602-0.5718, and the elongation at break is 1100%-1580%.
[0017] A method for preparing the polyurethane with multiple dynamic bonds and self-repairing properties according to the present invention comprises the following steps:
[0018] (1) Under nitrogen protection, the dehydrated polydiol, diisocyanate and anhydrous toluene are mixed, and stirred at 80-85° C. for 3-4 hours to obtain a prepolymer;
[0019] (2) adding an anhydrous toluene solution of a pyridine chain extender to the prepolymer, and continuing to stir and react at 80 to 85° C. for 8 to 10 hours to obtain a pyridine chain-extended polymer solution;
[0020] (3) adding an anhydrous toluene solution of catechol to the polymer solution, stirring and reacting at 45-55° C. for 12-14 hours to obtain a polyurethane matrix prepolymer solution;
[0021] (4) Adding the polyurethane matrix prepolymer solution into the trivalent iron ion salt solution, stirring for 20 to 30 minutes, pouring into a mold, and curing at 75 to 85° C. for more than 7 days to obtain a polyurethane with multi-dynamic bond synergistic self-healing properties.
[0022] Beneficial Effects
[0023] The present invention provides a polyurethane with multi-dynamic bond synergistic self-repairing, wherein the polyurethane elastomer is composed of 2,6-pyridine dimethanol as a chain extender, and the end group is composed of exposed catechol after dopamine capping. The iron ion has two functions: on the one hand, as a metal ligand with catechol, it forms a metal coordination bond with the catechol group at the end of the polymer chain. The metal coordination bond, as a dynamic chemical bond, can be broken when the material is damaged by the outside world, and can be re-formed when the fracture is connected; on the other hand, as a ligand of the pyridine ring, the lone pair of electrons on the nitrogen atom of pyridine can enter the empty orbit of the iron ion, thereby forming a coordination bond; this pyridine-iron ion coordination is also a dynamic chemical bond. Since the iron ion brings a large number of dynamic chemical bonds to the inside of the elastomer, this multi-level dynamic chemical bond gives the material a strong self-repairing ability.
[0024] The present invention provides a polyurethane with multi-dynamic bond cooperative self-repairing properties. Trivalent iron ions can simultaneously form coordination bonds with pyridine and catechol substances to form a complex cross-linking network. The presence of high-density multi-level dynamic chemical bonds inside the polyurethane elastomer gives the material a high self-repairing efficiency. In addition, since the polyurethane elastomer contains a large number of dynamic chemical bonds, the molecular chains have strong mobility and greater friction, so the damping performance of the material is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the reaction process of steps (1) to (4) in Example 1.
[0026] Figure 2 This is the infrared test result of PDM / DA-FePU in Example 1.
[0027] Figure 3 1-2 and Example 1 are stress-strain curves of the polyurethane.
[0028] Figure 4 The dynamic thermomechanical curves of the polyurethane in Comparative Example 1 and Example 1.
[0029] Figure 5 This is the stress-strain curve of PDM / DA-FePU before and after self-repair in Example 1. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with specific embodiments.
[0031] Comparative Example 1
[0032] The molecular weight of the polybutylene glycol in this comparative example is 1000.
[0033] (1) Under nitrogen protection, 20 g of polybutylene glycol was added to a 250 ml three-necked flask, the temperature was raised to 120° C., and the mixture was stirred at a rate of 200 r / min for 4 h to remove water. The mixture was then allowed to stand at room temperature to obtain dehydrated polybutylene glycol.
[0034] (2) 11.11 g of isophorone diisocyanate was weighed into the three-necked flask in step (1), 100 ml of anhydrous toluene was added to dissolve the raw materials, 0.02 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the mixture was stirred at a rate of 200 r / min and reacted for 4 h to obtain a prepolymer solution.
[0035] (3) Take 4.17 g of 2,6-pyridine dimethanol powder, dissolve it in 10 ml of anhydrous toluene in advance, add it into a three-necked flask after it dissolves, and continue to react at 80°C and 200 r / min for 8 h to obtain a light yellow transparent liquid.
[0036] (4) Take 2.012 g of dopamine hydrochloride in 10 ml of anhydrous toluene, stir to dissolve, then measure 1.08 g of triethylamine to adjust the pH value, let the solution in step (3) stand at 50° C., then add the dissolved dopamine hydrochloride / triethylamine mixed solution, and react at 150 r / min and 50° C. for 24 hours to obtain a light yellow transparent liquid.
[0037] (5) Pour the light yellow liquid obtained in step (4) into a polytetrafluoroethylene mold, place it in an oven at 80°C for one day and night to remove a large amount of toluene, and then place it in a vacuum oven at 80°C for 3 days to obtain a light yellow transparent polyurethane elastomer film PDM / DA-PU.
[0038] According to infrared testing, the structural formula of the PDM / DA-PU is as follows, wherein m represents the degree of polymerization of polybutylene glycol:
[0039]
[0040] Comparative Example 2
[0041] The molecular weight of the polybutylene glycol in this comparative example is 1000.
[0042] (1) Under nitrogen protection, 20 g of polybutylene glycol was added to a 250 ml three-necked flask, the temperature was raised to 120° C., and the mixture was stirred at a rate of 200 r / min for 4 h to remove water. The mixture was then allowed to stand at room temperature to obtain dehydrated polybutylene glycol.
[0043] (2) 11.11 g of isophorone diisocyanate was weighed into the three-necked flask in step (1), 100 ml of anhydrous toluene was added to dissolve the raw materials, 0.02 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the mixture was stirred at a rate of 200 r / min and reacted for 4 h to obtain a prepolymer solution.
[0044] (3) Take 4.17 g of 2,6-pyridine dimethanol powder, dissolve it in 10 ml of anhydrous toluene in advance, add it into a three-necked flask after it dissolves, and continue to react at 80°C and 200 r / min for 8 h to obtain a light yellow transparent liquid.
[0045] (4) Take 2.42 g of anhydrous ferric chloride and dissolve it in anhydrous toluene. After the temperature of the solution in step (3) drops to room temperature, add it into a three-necked flask and stir it at 200 r / min for 20 min at room temperature.
[0046] (5) The black liquid obtained in step (4) was poured into a polytetrafluoroethylene mold, placed in an oven at 80° C. for one day and night to remove a large amount of toluene, and then placed in a vacuum oven at 80° C. for 3 days to obtain a black polyurethane elastomer film, which was recorded as PDM-FePU.
[0047] According to infrared testing, the main chain structure of the PDM-FePU is as follows, where n represents the degree of polymerization of polybutylene glycol:
[0048]
[0049] The coordination relationship between iron ion and pyridine is as follows:
[0050]
[0051] Example 1
[0052] The molecular weight of the polybutylene glycol in this embodiment is 1000.
[0053] (1) Under nitrogen protection, 20 g of polybutylene glycol was added to a 250 ml three-necked flask, the temperature was raised to 120° C., and the mixture was stirred at a rate of 200 r / min for 4 h to remove water. The mixture was then allowed to stand at room temperature to obtain dehydrated polybutylene glycol.
[0054] (2) 11.11 g of isophorone diisocyanate was weighed into the three-necked flask in step (1), 100 ml of anhydrous toluene was added to dissolve the raw materials, 0.02 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the mixture was stirred at a rate of 200 r / min and reacted for 4 h to obtain a prepolymer solution.
[0055] (3) Take 2.085 g of 2,6-pyridine dimethanol powder, dissolve it in 10 ml of anhydrous toluene in advance, add it into a three-necked flask after it dissolves, and continue to react at 80°C and 200 r / min for 8 h to obtain a light yellow transparent liquid.
[0056] (4) Take 1.896 g of dopamine hydrochloride in 10 ml of anhydrous toluene, stir to dissolve, then measure 1.01 g of triethylamine to adjust the pH value, let the solution in step (3) stand at 50° C., then add the dissolved dopamine hydrochloride / triethylamine mixed solution, and react at 150 r / min and 50° C. for 24 hours to obtain a light yellow transparent liquid.
[0057] (5) Take 2.12 g of anhydrous ferric chloride and dissolve it in anhydrous toluene. After the temperature of the solution in step (4) drops to room temperature, add it into a three-necked flask and stir it at 200 r / min for 20 min at room temperature.
[0058] (6) The black liquid from step (5) was poured into a polytetrafluoroethylene mold, placed in an oven at 80°C for one day and night to remove a large amount of toluene, and then placed in a vacuum oven at 80°C for 3 days to obtain a black polyurethane elastomer film, which was recorded as PDM / DA-FePU.
[0059] The reaction process of steps (1) to (4) is as follows: Figure 1 shown.
[0060] like Figure 2 As shown, after infrared testing, the structural formula of the PDM / DA-FePU is as follows:
[0061]
[0062] Among them, the main chain structure is:
[0063]
[0064] The coordination relationships of iron ions are:
[0065] Example 2
[0066] The molecular weight of the polybutylene glycol in this embodiment is 1700.
[0067] (1) Under nitrogen protection, 34 g of polybutylene glycol was added to a 250 ml three-necked flask, the temperature was raised to 120° C., and the mixture was stirred at a rate of 200 r / min for 4 h to remove water. The mixture was then allowed to stand at room temperature to obtain dehydrated polybutylene glycol.
[0068] (2) 10.92 g of isophorone diisocyanate was weighed into the three-necked flask in step (1), 100 ml of anhydrous toluene was added to dissolve the raw materials, 0.02 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the mixture was stirred at a rate of 200 r / min and reacted for 4 h to obtain a prepolymer solution.
[0069] (3) Take 2.045 g of 2,6-pyridine dimethanol powder, dissolve it in 10 ml of anhydrous toluene in advance, add it into a three-necked flask after it dissolves, and continue to react at 80°C and 200 r / min for 8 h to obtain a light yellow transparent liquid.
[0070] (4) Take 1.916 g of dopamine hydrochloride in 10 ml of anhydrous toluene, stir to dissolve, then measure 1.12 g of triethylamine to adjust the pH value, let the solution in step (3) stand at 50° C., then add the dissolved dopamine hydrochloride / triethylamine mixed solution, and react at 150 r / min and 50° C. for 24 hours to obtain a light yellow transparent liquid.
[0071] (5) Take 2.24 g of anhydrous ferric chloride and dissolve it in anhydrous toluene. After the temperature of the solution in step (4) drops to room temperature, add it into a three-necked flask and stir it at 200 r / min for 20 min at room temperature.
[0072] (6) The black liquid from step (5) was poured into a polytetrafluoroethylene mold, placed in an oven at 80°C for one day and night to remove a large amount of toluene, and then placed in a vacuum oven at 80°C for 3 days to obtain a black polyurethane elastomer film, which was recorded as PDM / DA-FePU-2.
[0073] The structural formula of PDM / DA-FePU-2 is similar to that of Example 1, and the only difference is the degree of polymerization of polybutylene glycol.
[0074] Example 3
[0075] The molecular weight of the polybutylene glycol in this embodiment is 2000.
[0076] (1) Under nitrogen protection, 40 g of polybutylene glycol was added to a 250 ml three-necked flask, the temperature was raised to 120° C., and the reduced pressure was stirred at a rate of 200 r / min for 4 h to remove water, and then the mixture was allowed to stand at room temperature to obtain dehydrated polybutylene glycol.
[0077] (2) 11.12 g of isophorone diisocyanate was weighed into the three-necked flask in step (1), 100 ml of anhydrous toluene was added to dissolve the raw materials, 0.02 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the mixture was stirred at a rate of 200 r / min and reacted for 4 h to obtain a prepolymer solution.
[0078] (3) Take 2.055 g of 2,6-pyridine dimethanol powder, dissolve it in 10 ml of anhydrous toluene in advance, add it into a three-necked flask after it dissolves, and continue to react at 80°C and 200 r / min for 8 h to obtain a light yellow transparent liquid.
[0079] (4) Take 1.926 g of dopamine hydrochloride in 10 ml of anhydrous toluene, stir to dissolve, then measure 1.12 g of triethylamine to adjust the pH value, let the solution in step (3) stand at 50° C., then add the dissolved dopamine hydrochloride / triethylamine mixed solution, and react at 150 r / min and 50° C. for 24 hours to obtain a light yellow transparent liquid.
[0080] (5) Take 2.34 g of anhydrous ferric chloride and dissolve it in anhydrous toluene. After the temperature of the solution in step (4) drops to room temperature, add it into a three-necked flask and stir it at 200 r / min for 20 min at room temperature.
[0081] (6) The black liquid from step (5) was poured into a polytetrafluoroethylene mold, placed in an oven at 80°C for one day and night to remove a large amount of toluene, and then placed in a vacuum oven at 80°C for 3 days to obtain a black polyurethane elastomer film, which was recorded as PDM / DA-FePU-3.
[0082] The structural formula of PDM / DA-FePU-3 is similar to that of Example 1, and the only difference is the degree of polymerization of polybutylene glycol.
[0083] Example 4
[0084] The molecular weight of polyethylene glycol in this embodiment is 2000.
[0085] (1) Under nitrogen protection, 36 g of polyethylene glycol was added to a 250 ml three-necked flask, the temperature was raised to 120° C., and the reduced pressure was stirred at a rate of 200 r / min for 4 h to remove water, and then the mixture was allowed to stand at room temperature to obtain dehydrated polyethylene glycol.
[0086] (2) 11.08 g of isophorone diisocyanate was weighed into the three-necked flask in step (1), 100 ml of anhydrous toluene was added to dissolve the raw materials, 0.02 g of dibutyltin dilaurate was added, the temperature was raised to 80° C., and the mixture was stirred at a rate of 200 r / min and reacted for 4 h to obtain a prepolymer solution.
[0087] (3) Take 2.045 g of 2,6-pyridine dimethanol powder, dissolve it in 10 ml of anhydrous toluene in advance, add it into a three-necked flask after it dissolves, and continue to react at 80°C and 200 r / min for 8 h to obtain a light yellow transparent liquid.
[0088] (4) Take 1.856 g of dopamine hydrochloride in 10 ml of anhydrous toluene, stir to dissolve, then measure 0.98 g of triethylamine to adjust the pH value, let the solution in step (3) stand at 50° C., then add the dissolved dopamine hydrochloride / triethylamine mixed solution, and react at 150 r / min and 50° C. for 24 hours to obtain a light yellow transparent liquid.
[0089] (5) Take 2.14 g of anhydrous ferric chloride and dissolve it in anhydrous toluene. After the temperature of the solution in step (4) drops to room temperature, add it into a three-necked flask and stir it at 200 r / min for 20 min at room temperature.
[0090] (6) The black liquid from step (5) was poured into a polytetrafluoroethylene mold, placed in an oven at 80°C for one day and night to remove a large amount of toluene, and then placed in a vacuum oven at 80°C for 3 days to obtain a black polyurethane elastomer film, which was recorded as PDM / DA-FePU-6.
[0091] Comparative Example 3
[0092] The difference between this comparative example and Example 1 is that the consumption of anhydrous ferric chloride is 3.00 g.
[0093] The final products prepared in the examples and comparative examples were subjected to a tensile test. The test conditions were as follows: a 500N mechanical sensor was used, a dumbbell-shaped cutter with a size of 4mm*50mm was used to cut the samples, and the test was carried out at a tensile rate of 20mm / min. The results are shown in FIG. Figure 3 As shown, it can be concluded that the strength of the polyurethane elastomer using pyridine chain extension is positively correlated with the content of pyridine on the main chain, and iron ions can be used as cross-linking points to further improve the strength of the material, which shows that the iron ion cross-linked polyurethane elastomer based on pyridine chain extension can be used as a synthesis method of a class of polyurethane elastomers to improve the mechanical properties of polyurethane elastomers. The addition of iron ions can improve the strength and elongation at break of the material, which shows that the introduction of iron ion-pyridine coordination and iron ion-catechol is conducive to the improvement of material strength.
[0094] The damping performance test was carried out on the final products prepared in the examples and comparative examples. The specific implementation method is as follows: take a piece of prepared PDM / DA-FePU and cut it into 10mm*10mm strips with a cutter. Then a dynamic mechanical analysis (DMA) test was carried out in an air environment. The sample was fixed by a shear clamp. The test adopted a dynamic temperature scanning mode. The heating rate was set to 3℃ / min. The frequency was set to 10Hz, which was used to evaluate the thermodynamic behavior of the sample between -80℃ and 80℃. The results are shown in Figure 4 shown.
[0095] The final product prepared in the embodiment was subjected to a tensile self-repair test. The specific implementation method was as follows: a piece of prepared PDM / DA-FePU was taken, cut into a dumbbell shape with a cutter, and then the middle part was cut with a knife, and then tightly fitted for 10 seconds. It was found that there was no obvious cut mark at the fracture. At this time, it can be considered that the sample has completed the self-repair process. The results are as follows Figure 5 shown.
[0096] It can be seen from the results of Example 1 and Comparative Example 3 that with the increase of iron ion concentration, new coordination bonds are continuously generated in the system, the cross-linking point density is increased, and the mechanical properties are improved; however, when all the catechol and pyridine form a stable coordination relationship with the iron ions, the iron ions added later have no coordination groups that can adapt to them, so they can only exist in the elastomer in the form of small molecules, acting as a "plasticizer", resulting in a decrease in the mechanical properties of the material.
[0097] The self-healing performance of PDM / DA-FePU-1 at 25°C in Example 1 is shown in Table 1.
[0098] Table 1
[0099]
[0100] The performance results of the materials obtained in the examples and comparative examples are shown in Table 2.
[0101] Table 2
[0102]
[0103] The performance results of the materials obtained in the examples and comparative examples are shown in Table 3.
[0104] Table 3
[0105] Soft segment type Soft segment molecular weight Damping factor PDM / DA-FePU-1 Polybutylene glycol 1000 0.5718 PDM / DA-FePU-2 Polybutylene glycol 1700 0.5374 PDM / DA-FePU-3 Polybutylene glycol 2000 0.4861 PDM / DA-FePU-4 Polyethylene glycol 2000 0.4725 PDM / DA-PU Polybutylene glycol 1000 0.4602
[0106] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A polyurethane with multiple dynamic bonds and self-repairing function, characterized in that: The raw material composition of the polyurethane comprises polydiol, diisocyanate, pyridine chain extender, catechol and trivalent iron ion salt. Taking the total mass of the polydiol, diisocyanate, pyridine chain extender and catechol as 100%, the mass fraction of the polydiol is 46.65% to 54.24%, the mass fraction of the diisocyanate is 25.91% to 32.51%, the mass fraction of the pyridine chain extender is 9.72% to 13.59%, and the mass fraction of the catechol is 7.69% to 14.91%; the molar ratio of iron ion, pyridine chain extender and catechol is 1:2:
3.
2. A polyurethane with multiple dynamic bonds and self-repairing as claimed in claim 1, characterized in that: The main chain of the polyurethane is formed by chain extension of polydiol and diisocyanate by pyridine chain extender, and the end group is exposed by catechol group after end-capping by catechol substance. The trivalent iron ion forms a metal coordination bond with the catechol group on the one hand, and forms a coordination bond with the nitrogen atom on pyridine on the other hand; wherein the coordination relationship between the iron ion and the catechol group is: The coordination relationship of iron ion to pyridine is 3. A polyurethane with multiple dynamic bonds and self-repairing properties as claimed in claim 1 or 2, characterized in that: The polyglycol is one or more of polybutylene glycol, polypropylene glycol and polyethylene glycol.
4. A polyurethane with multiple dynamic bonds and self-repairing properties as claimed in claim 1 or 2, characterized in that: The molecular weight of the polyglycol is 1500-3000.
5. A polyurethane with multiple dynamic bonds and self-repairing properties as claimed in claim 1 or 2, characterized in that: The diisocyanate is one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate and L-lysine diisocyanate.
6. A polyurethane with multiple dynamic bonds and self-repairing properties as claimed in claim 1 or 2, characterized in that: The pyridine chain extender is 2,6-pyridine dimethanol or 2,6-pyridine dimethylamine.
7. A polyurethane with multiple dynamic bonds and self-repairing properties as claimed in claim 1 or 2, characterized in that: The catechol substance is one or more of dopamine, isoproterenol, ellagic acid and quercetin.
8. A polyurethane with multiple dynamic bonds and self-repairing properties as claimed in claim 1 or 2, characterized in that: The trivalent iron ion salt is one or more of nitrate, carboxylate and chloride.
9. A polyurethane with multiple dynamic bonds and self-repairing properties as claimed in claim 1 or 2, characterized in that: The tensile strength of the polyurethane is 0.9-3.5 MPa, the damping factor is 0.4602-0.5718, and the elongation at break is 1100%-1580%.
10. A method for preparing a polyurethane with multiple dynamic bonds and self-repairing properties as claimed in any one of claims 1 to 9, the method comprising: (1) Under nitrogen protection, the dehydrated polydiol, diisocyanate and anhydrous toluene are mixed, and stirred at 80-85° C. for 3-4 hours to obtain a prepolymer; (2) adding an anhydrous toluene solution of a pyridine chain extender to the prepolymer, and continuing to stir and react at 80 to 85° C. for 8 to 10 hours to obtain a pyridine chain-extended polymer solution; (3) adding an anhydrous toluene solution of catechol to the polymer solution, stirring and reacting at 45-55° C. for 12-14 hours to obtain a polyurethane matrix prepolymer solution; (4) Adding the polyurethane matrix prepolymer solution into the trivalent iron ion salt solution, stirring for 20 to 30 minutes, pouring into a mold, and curing at 75 to 85° C. for more than 7 days to obtain a polyurethane with multi-dynamic bond synergistic self-healing properties.
Citation Information
Patent Citations
High-strength room-temperature self-repairing polyurethane elastomer based on multiple dynamic reversible effects as well as preparation and application of high-strength room-temperature self-repairing polyurethane elastomer
CN110790888A
Metal coordination self-healing polyurethane elastomer and preparation method thereof
CN111217985A
Polyphenolic compound modified polyurethane elastomer and preparation method thereof
CN116143995A
Preparation method of coordination-enhanced disulfide type self-repairing polyurethane urea
CN117487126A
Dipyrazole-based metal coordination self-repairing polyurethane elastomer and preparation method thereof
CN117843913A
Cited By
A heat-resistant self-repairing polyurethane elastic system and preparation method thereof
CN120289748B
Novel pyridyl modified polyferric flocculant as well as preparation method and application thereof
CN120328712A
Energy-containing self-repairing functional polyurethane and preparation method thereof
CN122520882A